Analisis Kurikulum Paud Dalam Meningkatkan Kreativitas Anak Usia Dini - winta, windira; Loka, Novita (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The Early Childhood Education (ECE) curriculum plays a crucial role in supporting the development of creativity and intelligence in children. This study aims to analyze the effectiveness of the ECE curriculum in enhancing children's creativity through a descriptive qualitative approach. Data were collected from interviews with educators, parents, and observations of activities in several ECE institutions. The results indicate that curricula integrating play, art, and exploration activities significantly improve children's critical and innovative thinking abilities. However, challenges such as limited facilities and a lack of understanding of creative approaches still persist. Recommendations include the need for collaboration between educational institutions and parents, as well as enhanced training for educators to create a more supportive learning environment. This research is expected to contribute to the development of a more adaptive and responsive ECE curriculum that meets children's needs.